Research note on the social and economic life of village people in central Java: A Case Study of Two Villages in Yogyakarta Special Region - Haruo Kuroyanagi. (Faculty of Geography, Universitas Gadjah Mada, 1990)
This is a tentative research note of the field-work which was conducted under the title of